The Application and Exploration of Chinese Opera Club in School Aesthetic Education from the Perspective of Aesthetic Education Infiltration - Xu, Jue (Journal of Social Science and Humanities, 2025)
As an important component of the “Five-Education Integration” strategy, aesthetic education is a key approach to shaping students’ sound personality and pure heart. In December 2023, the Ministry of Education issued the “Notice on Fully Implementing the School Aesthetic Education Immersion Action”, clearly stating the task goals and specific measures of aesthetic education, emphasizing the creation of diverse art clubs to enrich campus culture and enhance students’ aesthetic literacy. With the in-depth advancement of the “Opera Enters Campus” policy, schools in Jinhua region have actively integrated Wu Opera art into daily teaching and activities, responding to the call of “aesthetic education immersion”, cultivating students’ aesthetic sentiments and enhancing their aesthetic literacy through the profound cultural heritage of opera art, laying a solid foundation for students’ all-round development. This study aims to explore the application and exploration of opera clubs in school aesthetic education and propose strategies to enhance the effectiveness of aesthetic education in opera clubs.